There is Neither Old Nor Young? Early Christianity and Ancient Ideologies of Age - Barclay, John M. G. (New Testament studies, 2007)
Instructions given to the ‘older’ and ‘younger’ in some early Christian texts prompt inquiry into the rationale for this polarity and its ideological freight. Demographics suggest that the adult population rarely contained more than two generations, and comparative study indicates that where age was marked these categories usually sufficed. Their ambiguity and flexibility made them suited to ideological deployment, legitimating the power of the ‘older’. 1 Peter, 1 Clement, the Pastorals, and Polycarp demonstrate this phenomenon in early Christianity, with 1 Tim 4.12 and Ignatius Mag. 3.1 as exceptions that prove the rule. But why are age qualifications absent from the authentic Paulines?